2015
DOI: 10.1680/jenes.15.00018
|View full text |Cite
|
Sign up to set email alerts
|

Soybean peroxidase-catalysed removal of benzidines from water

Abstract: Crude soybean peroxidase (SBP), isolated from soybean seed coats (hulls) at unusually low concentrations, catalyses the oxidative polymerisation of hazardous aqueous benzidine and its 3,3′-dichloro, 3,3′-dimethyl and 3,3′-dimethoxy derivatives in the presence of hydrogen peroxide. The optimum operating conditions for oxidation of 0·10 mM benzidine were investigated. At pH 5, the hydrogen peroxide-to-substrate concentration ratio was 1·5 and the minimum SBP concentration required to achieve at least 95% convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Also, it is noted that benzidine conversion would not be the ''limiting factor'' (because it requires much less enzyme concentration than aniline). This lower requirement for benzidine as SBP substrate was reported by Malik Altahir et al (2015) where 0.10 mM benzidine required 0.43 mU/mL SBP.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Also, it is noted that benzidine conversion would not be the ''limiting factor'' (because it requires much less enzyme concentration than aniline). This lower requirement for benzidine as SBP substrate was reported by Malik Altahir et al (2015) where 0.10 mM benzidine required 0.43 mU/mL SBP.…”
Section: Resultsmentioning
confidence: 48%
“…It can be observed that the optimum pH was 5.0 for total amines as well as aniline and benzidine. For authentic aniline and benzidine optimum pHs with SBP have also been reported as pH 5.0 (Malik Altahir et al, 2015;Mazloum et al, 2016); thus, further experiments in this research (enzyme and H 2 O 2 optimization) were done at this pH. Also, it is noted that benzidine conversion would not be the ''limiting factor'' (because it requires much less enzyme concentration than aniline).…”
Section: Resultsmentioning
confidence: 88%
“…Mukherjee et al . found pH 4.6 to be optimal for removal of p ‐cresidine (pK a 4.7) using SBP 22 and pH 5.0 optimal for removal of benzidine using SBP 23 . Thus, the optimal pH for enzymatic treatment is close to the pK a of anilino compounds.…”
Section: Resultsmentioning
confidence: 98%
“…The sample dilution was adjusted according to the expected enzyme activity (to have approximately 0.2 absorbance change in 30 seconds). 35 One unit of SBP activity is defined as the amount catalyzing 1 μmol of hydrogen peroxide conversion per minute under the assay conditions. 29…”
Section: Soybean Peroxidase Activity Assaymentioning
confidence: 99%
“…Aliquots (5 mL) were withdrawn by micropipette at various time intervals, quenched with 0.25 mL catalase solution and then centrifuged, micro-filtered and analyzed by a spectrophotometer. Centrifugation was used for quick sample preparation in order to get a clear liquid sample 35.…”
mentioning
confidence: 99%